CORRELATION OF KNOWLEDGE AND ATTITUDE TOWARD HYPERTENSION SELF-MANAGEMENT PRACTICE DURING THE COVID-19 PANDEMIC - Nia Damiati; Mutiara Martin; Irma Nurbaeti; Mardiyanti (Universitas Airlangga, 2023)
Introduction: Restrictions on mobility during the COVID-19 pandemic have worsened lifestyle and made it harder for people with hypertension to manage their condition, which can lead to complications. Knowledge and attitude have a significant correlation toward hypertension self-management. This study aimed to determine the correlation between knowledge and attitudes of hypertensive patients toward hypertension self-management practice during the COVID-19 pandemic. Method: The method used was a descriptive-analytic correlation with a cross-sectional approach. The sample used was 50 hypertensive patients aged ≥ 15 years old, samples obtained through the accidental sampling technique. Data collection through the google form online questionnaire containing a modified Indonesian version of the Knowledge, Attitudes, and Practice Level of Hypertensive Patients on Lifestyle Modification questionnaire. Statistical test for bivariate using Pearson and Spearman correlation. Result: The study found that 54% respondents had good knowledge and practice, and 50% had a positive attitude toward hypertension self-management during the COVID-19 pandemic. Poor hypertension self-management practices include 56% of respondents did not exercise; 54% did not plan a diet to control blood pressure; 32% did not measure blood pressure regularly; and 46% did not take antihypertensive drugs. Bivariate analysis showed that there was a correlation between knowledge (p = 0.000; r = +0.320), and attitudes (p = 0.001; r = +0.471) toward hypertension self-management practice during the COVID-19 pandemic. Conclusion: The study results showed that the correlation is positive, but the strength of the correlation is weak. therefore, it is necessary to educate the public regarding hypertension and self-management during the COVID-19 pandemic, especially regarding the definition of hypertension, medication adherence, and lifestyle modifications to control hypertension. Keywords: Attitude; COVID-19; Hypertension; Knowledge; Self-management